Effects of sodium bicarbonat ingestion on swim performance in youth athletes - Zajac, A.; Cholewa, J.; Poprzecki, S.; Waskiewicz, Z.; Langfort, J. (Journal of Sports Science & Medicine, 2009)
The purpose of this study was to evaluate the effect of oral administration of sodium bicarbonate (300 mg·kg-1 b.w.) on swim performance in competitive, (training experience of 6.6 ± 0.6 years) youth, (15.1 ± 0.6 years) male swimmers. The subjects completed a test trial, in a double blind fashion, on separate days, consisting of 4 x 50m front crawl swims with a 1st minute passive rest interval twice, on two occasions: after ingestion of bicarbonate or placebo, 72 hours apart, at the same time of the day. Blood samples were drawn from the finger tip three times during each trial; upon arrival to the laboratory, 60 min after ingestion of placebo or the sodium bicarbonate solution and after the 4 x 50m test, during the 1st min of recovery. Plasma lactate concentration, blood pH, standard bicarbonate and base excess were evaluated. The total time of the 4 x 50 m test trial improved from 1.54.28 to 1.52.85s, while statistically significant changes in swimming speed were recorded only during the first 50m sprint (1.92 vs. 1.97 m·s-1, p < 0.05). Resting blood concentration of HCO-3 increased following the ingestion of sodium bicarbonate from 25.13 to 28.49 mM (p < 0.05). Sodium bicarbonate intake had a statistically significant effect on resting blood pH (7.33 vs. 7.41, p < .05) as well as on post exercise plasma lactate concentration (11.27 vs. 13.06 mM, p < 0.05)). Collectively, these data demonstrate that the ingestion of sodium bicarbonate in youth athletes is an effective buffer during high intensity interval swimming and suggest that such a procedure can be used in youth athletes to increase training intensity as well as swimming performance in competition at distances from 50 to 200 m.